THE LEADERSHIP OF ABUYA IN CONFLICT MANAGEMENT AT MTI PASIR ISLAMIC BOARDING SCHOOL - Rini Agustin; Nurhizrah Gistituati; Rusdinal Rusdinal (Universitas Pendidikan Indonesia, 2021)
This article departs from the assumption that leadership in Islamic boarding schools applies an authoritarian-paternalistic and laissez-faire leadership model, making it less effective. This article used a descriptive analysis approach, this article analyzes the Abuya (leader) leadership model at the MTI Pasir Islamic Boarding School in managing conflict. This article finds that Abuya not applies authoritarian-paternalistic and laissez-faire leadership, but charismatic-democratic. When a conflict occurs, Abuya with his charisma brings together the conflicting parties and conducts deliberation and consensus. The conflict management carried out by Abuya was able to provide positive energy for the development and progress of the MTI Pasir Islamic Boarding School.